The techlash and tech crisis communication - Weiss-Blatt, Nirit (Emerald Publishing Limited, 2021)
This book provides an in-depth analysis of the evolution of tech journalism. The emerging tech-backlash is a story of pendulum swings: We are currently in tech-dystopianism after a long period spent in tech-utopianism. Tech companies were used to 'cheerleading' coverage of product launches. This long tech-press honeymoon ended, and was replaced by a new era of mounting criticism focused on tech's negative impact on society. When and why did tech coverage shift? How did tech companies respond to the rise of tech criticism? The book depicts three main eras: Pre-Techlash, Techlash, and Post-Techlash. The reader is taken on a journey from computer magazines, through tech blogs to the upsurge of tech investigative reporting. It illuminates the profound changes in the power dynamics between the media and the tech giants it covers. The interplay between tech journalism and tech PR was underexplored. Through analyses of both tech media and the corporates' crisis responses, this book examines the roots and characteristics of the Techlash, and provides explanations to 'How did we get here?'. Insightful observations by tech journalists and tech public relations professionals are added to the research data, and together - they tell the story of the TECHLASH. It includes theoretical and practical implications for both tech enthusiasts and critics.